Finalidades e Fundamento das Clinicas de Prevenção e Diagnóstico do Câncer - Marsillac, Jorge de (2023)
Report presented to the First Latin-American Conference about Early Diagnosis in Cancer held at Bogotá, in 1960. The author resumes the history of fight against cancer in Brazil noting the first private iniciatives and the creation of the National Cancer Service beloniging to the Ministry of Health, in 1941. He shows the results of 5 years cure quoting the gradually improvement due, as in others countries, to the intense popular propaganda, formation of technical personal and installation of spreading detection clinics specially in ginecological cancer. The main hospitais and clinics are described by the author as well as the used technics.